Analisis Faktor Non Medis yang Mempengaruhi Terjadinya Persalinan Sectio Caesarea di Rumah Sakit Umum Daerah dr. Adjidarmo Kabupaten Lebak Tahun 2024 - Ayu Resky Mustafa; Popi Sri Wahyuni (Jurnal Ners, 2025)
Sectio caesarea (CS) has been proven to reduce maternal mortality when vaginal delivery is indicated as risky such as prolonged labor, fetal distress, and fetal malpresentation. In addition to these medical factors, the incidence of Sectio caesarea (CS) can also be caused by non-medical factors. This study aims to analyze non-medical factors that influence the occurrence of sectio caesarea at the Dr. Adjidarmo Regional General Hospital, Lebak Regency. This study is a quantitative study with a descriptive analytical design. Using a cross-sectional method with primary data from questionnaires. Data analysis using the Pearson correlation analysis test using 95% confidence, and a significance value of 0.05. This study was conducted at the Dr. Adjidarmo Regional General Hospital, Lebak Regency on December 16 - December 31, 2024. The population in this study were pregnant women who would undergo a cesarean section as many as 168 people with a sample size of 62 people. The results of the study showed that there were variables that had a correlation with the incidence of cesarean sections, namely the age variable (sign 0.002), Parity (sign 0.011), Childbirth history (sign 0.000), knowledge (sign 0.000), anxiety (sign 0.013) and husband's support (sign 0.001). Meanwhile, the variables Education, income and occupation have a sign value > 0.05. Which means there is no correlation.There is a relationship between non-medical factors and the occurrence of cesarean section delivery at the Dr. Adjidarmo Regional General Hospital, Lebak Regency in 2024